2014
DOI: 10.14745/ccdr.v40is2a06
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-resistant Campylobacter in broiler chicken in Canada

Abstract: This case study outlines the patterns of ciprofloxacin resistance in Campylobacter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…This result is likely related to the extensive use of fluoroquinolones and tetracyclines that could be responsible for the emergence of resistant Campylobacter isolates as reported by other studies (Aarestrup and Engberg 2001;Ge et al 2013). Moreover, we observed differences in antimicrobial resistance between C. coli and C. jejuni, with the latter being generally more susceptible, accordingly to several works (Jore et al 2010;Haruna et al 2012;Pollett et al 2012;Agunos et al 2013; Ge et al 2013; Wieczorek et al 2013). Our results showed that the 30% of C. coli isolates were resistant to erythromycin, whereas all isolates of C. jejuni were susceptible.…”
Section: Discussionsupporting
confidence: 75%
“…This result is likely related to the extensive use of fluoroquinolones and tetracyclines that could be responsible for the emergence of resistant Campylobacter isolates as reported by other studies (Aarestrup and Engberg 2001;Ge et al 2013). Moreover, we observed differences in antimicrobial resistance between C. coli and C. jejuni, with the latter being generally more susceptible, accordingly to several works (Jore et al 2010;Haruna et al 2012;Pollett et al 2012;Agunos et al 2013; Ge et al 2013; Wieczorek et al 2013). Our results showed that the 30% of C. coli isolates were resistant to erythromycin, whereas all isolates of C. jejuni were susceptible.…”
Section: Discussionsupporting
confidence: 75%
“…The high level of resistance observed here against tetracycline further supports the role of poultry in the dissemination of AMR to humans, since tetracycline is not commonly used in clinical medicine in Belgium, but is more routinely used for veterinary purposes as a therapeutic and preventive agent in poultry [57]. The role of poultry consumption in the antimicrobial resistance of clinical Campylobacter strains is further supported by different observational studies in other European countries, such as the Netherlands and Spain, and in the United States and Canada that linked the rise of fluoroquinolone-resistant C. jejuni infections in humans with the introduction of fluoroquinolones in poultry therapy [23,58]. A similar observation was noted in the with the emergence of fluoroquinolone-resistant Campylobacter following the approval of fluoroquinolones as growth promoters in veterinary practices [59].…”
Section: Discussionmentioning
confidence: 99%
“…Many AMRs will decline following cessation or marked reduction in the use of relevant drugs, such as has been observed among Dutch isolates of E. coli and Campylobacter in the last decade following stringent control of antimicrobial use in agriculture (RIVM, , p. 80). However, by contrast, FQ resistance among isolates of Campylobacter in North America and Denmark has remained prevalent despite little or no recent use of FQ in the respective industries (Agunos et al., ; DANMAP, , p. 130)…”
Section: Control and Elimination Of Amr Organismsmentioning
confidence: 99%